Beyond risk, resilience, and dysregulation: Phenotypic plasticity and human development - Belsky, Jay; Pluess, Michael (Development and psychopathology, 2013)
We provide a theoretical and empirical basis for the claim that individual differences exist in developmental plasticity and that phenotypic plasticity should be a subject of study in its own right. To advance this argument, we begin by highlighting challenges that evolutionary thinking poses for a science of development and psychopathology, including for the diathesis–stress framework that has (fruitfully) guided so much empirical inquiry on developmental risk, resilience, and dysregulation. With this foundation laid, we raise a series of issues that the differential-susceptibility hypothesis calls attention to, while highlighting findings that have emerged over just the past several years and are pertinent to some of the questions posed. Even though it is clear that this new perspective on Person × Environment interaction is stimulating research and influencing how hypotheses are framed and data interpreted, a great many topics remain that need empirical attention. Our intention is to encourage students of development and psychopathology to treat phenotypic plasticity as an individual-difference construct while exploring unknowns in the differential-susceptibility equation.